PENGARUH KOMPENSASI TERHADAP KINERJA GURU - Nuroniyah, Mila; Anengsih, Aan; Patimah, Siti; Lugowi, Rifyal Ahmad (STKIP Pesisir Selatan, 2025)
The teacher plays an important role in the world of education, among his duties is to educate and educate the nation's children to become a superior generation in facing life's challenges in the future. In carrying out their duties as teachers, it is appropriate for teachers to get rewards for the services they have provided to the world of education. Rewards for these teachers are usually contained in the compensation system that has been regulated by educational institutions, both material compensation such as salaries, allowances, incentives, and so on, and non-material ones such as health insurance, a conducive work environment, supporting work facilities, etc. This is done with the intention that these teachers get proper compensation and can fulfill their daily needs. Providing appropriate compensation is expected to be able to support the performance of teachers in the educational institutions where they take shelter. This research was conducted to examine the effect of compensation on teacher performance which was carried out using the SLR (Systematic Literature Review) method, namely by identifying, reviewing, evaluating, and interpreting all previous studies that were closely related to teacher compensation and performance.